Maternal nutrition, fetal development and long-term health - Fleming, Tom (Henry Stewart Talks, 2019)
Early embryo development: the interplay between morphogenesis and the environment, Developmental Origins of Health and Disease (DOHaD) concept, How maternal nutrition influences events around conception and changes the programme of development, Maternal over or under-nutrition can both cause adverse health risk, Mechanistic understanding of how poor maternal nutrition leads to adult disease involving epigenetic, molecular, cellular, metabolic, and physiologic components